A PREDATION RECORD OF NABIS PARANENSIS (HEMIPTERA: HETEROPTERA) OVER AEDES ALBIFASCIATUS - Carvajal, Mariom A.; Jimenez, Nathaly; Faundez, Eduardo (My University, 2019)
Aedes albifasciatus is one of the most widely distributed mosquitoes in the Southern Cone of South America, and a known vector of western equine encephalomyelitus. Despite its wide range of distribution and relatively large abundance over its distribution, little is known about the ecological interactions in adults. In this contribution we record the first predation record of the damselbug Nabis paranensis (Nabidae) over an adult male of A. albifasciatus. The interaction record is analyzed and discussed.
Keywords: culicidae; interactions; nabidae; predatory; south america